Jürgen Moltmann's ethics of hope: eschatological possibilities for moral action - Harvie, Timothy (Ashgate new critical thinking in religion, theology, and biblical studies, 2009)
This book develops a thorough account of the sphere of human moral action in sustained dialogue with Jurgen Moltmann. By examining God's role as promise-giver, particularly in the Christian understanding of resurrection, this work describes the occupancy of both history and space in moral terms. This leads to an understanding of Jesus' description of 'the kingdom of God' to feature prominently in describing both the possibility and content of human moral action. By offering an account of each of the main doctrines found in Moltmann's corpus - the role of the future, the Trinity, the Holy Spirit, and anthropology - this book locates how each contributes to the understanding of ethics from a Christian perspective and subsequently applies these findings to the contemporary issue of poverty and global economics.